1999
DOI: 10.1016/s0920-5861(98)00366-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidation in a three-phase stirred airlift reactor: experiments and model

Abstract: The three-phase catalytic oxidation of glucose into gluconic acid is studied in a new type of reactor: a stirred internal-loop airlift reactor. The in¯uence of oxygen¯ow rate and of agitation on reaction rate are experimentally checked. By means of a model, a better knowledge of the reaction kinetic order for oxygen is reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…It can be easily recognized that gas velocity has a positive effect on reaction rate and with increasing gas velocity, the reaction rate increases. The results of this study are in agreement with those in literature [15,16] al. [15] concluded that the reaction rate depended on gas velocity for u G < 1.17 cm s -1 while it was independent of gas velocity for u G > 1.17 cm s -1 .…”
Section: Effect Of Gas Velocitysupporting
confidence: 94%
See 2 more Smart Citations
“…It can be easily recognized that gas velocity has a positive effect on reaction rate and with increasing gas velocity, the reaction rate increases. The results of this study are in agreement with those in literature [15,16] al. [15] concluded that the reaction rate depended on gas velocity for u G < 1.17 cm s -1 while it was independent of gas velocity for u G > 1.17 cm s -1 .…”
Section: Effect Of Gas Velocitysupporting
confidence: 94%
“…The results of this study are in agreement with those in literature [15,16] al. [15] concluded that the reaction rate depended on gas velocity for u G < 1.17 cm s -1 while it was independent of gas velocity for u G > 1.17 cm s -1 . In the present work, the range of gas velocity was between 0.14-1.12 cm s -1 which is less than 1.17 cm s -1 and the reaction rate was found to be affected by the gas velocity.…”
Section: Effect Of Gas Velocitysupporting
confidence: 94%
See 1 more Smart Citation
“…Different three-phase reaction systems are used for the evaluation of the reaction. Kinetic performances are mainly investigated in slurry reactors [11 -14], but spinning disc reactors [15], rotating foam reactors [11], or internal loop airlift reactors [16] are also used. Tschentscher et al [11] showed the influence of process conditions on the reactor performance.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of whole cells or glucose oxidase enzyme by various techniques has often been reported to be a useful approach to the production of gluconic acid or other microbial metabolites (Hartmeier and Döppner, 1983;Pronk et al 1989;Sakurai et al 1989;Gromada and Fiedurek, 1997;Nakao et al 1997;Kara and Bozdemir, 1998;Velizarov and Beschkov, 1998;Anastassiadis et al 1999;Sankpal et al 1999;Bang et al 1999;Ferraz et al 2000;Bao et al 2001;Blandino et al 2001;Klein et al 2002;Anastassiadis et al 2003;Godjevargova et al 2004;Anastassiadis et al 2005;Mukhopadhyay et al 2005). Fluidized bed reactors have been often used for several fermentation applications, in especially for anaerobic processes.…”
mentioning
confidence: 99%